The online learning readiness: technological skill readiness and gender impact / Salasiah M Said, Nor Famiza Tarsik and Raja Alwi Raja Omar - M Said, Salasiah; Tarsik, Nor Famiza; Raja Omar, Raja Alwi (2021)
Since the early year 2020, the world has been shocked by the COVID-19 outbreak. The COVID-19 pandemic has brought the world to a standstill, entire cities have been locked down, and people have been restricted to their homes to stop or slow the spread of this disease (Rafique, Mahmood, Warraich, & Rehman, 2021). This outbreak has affected people's daily routines. It is included social, career, economics, education, and so on. In terms of education, the minister had announced the different phases and methods to be adopted while academic institutions were closed. Most universities have transformed their way of teaching and learning environment. One of the teachings and learning methods is Open and Distance Learning (ODL). It was supported by Rafique, Mahmood, Warraich, and Rehman (2021) which stated that Corona Virus Disease or COVID-19 has changed the way of teaching and learning process. They explained that online learning provides a computer-mediating environment for sharing one's perspective with others confidently and comfortably. If both instructors and students connected virtually during the teaching and learning process, it can be assumed as an example of online learning. Nowadays, many media or platforms can be used by instructors or students such as social media. This was supported by Min-Ling, Chien, Chao-Hsiu, and Zang-Yuan (2010) who stated that an online course environment provides communication tools to facilitate interpersonal communication among teachers and students. Readiness is defined as being prepared mentally or physically for some experience or action (So & Swotman, 2006). It requires people to accept any form of teaching-learning method. Other than that, readiness is also defined as students' perception in delivery, self-confidence in using e-communication channels, and students' autonomy in learning participation (Yuk, et al., 2021). In addition, the Chapnick Readiness Model (2000) was used as the theoretical framework in the study Coopasami, Knight, and Pete (2017). This model groups different factors into eight readiness categories which are psychological readiness, sociological readiness, environmental readiness, human resource readiness, financial readiness, technological skill readiness, equipment readiness, and content readiness. However, this study only focuses on technological skill readiness among students.